2010
DOI: 10.1002/mrm.22653
|View full text |Cite
|
Sign up to set email alerts
|

MRI resolution enhancement: How useful are shifted images obtained by changing the demodulation frequency?

Abstract: Super-resolution reconstruction is a process by which a set of different low resolution images of the same object are used to create an enhanced, higher resolution image of that object. Recently there has been debate amongst researchers whether it is possible to obtain in-plane image enhancement using a set of low resolution magnetic resonance images, acquired by making small, independent changes to the demodulation frequency. We show that shifted low-resolution images contain different information that can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 16 publications
0
9
1
Order By: Relevance
“…Uecker and coworkers claim that our conclusion in Ref 1. was supported by neither the theoretical arguments nor the experimental data presented.…”
contrasting
confidence: 64%
See 2 more Smart Citations
“…Uecker and coworkers claim that our conclusion in Ref 1. was supported by neither the theoretical arguments nor the experimental data presented.…”
contrasting
confidence: 64%
“…Furthermore, comparison of Fig. 4(a) to (b) in Ref 1. shows that enhancement is most observable at object features, where dimensions are near the effective width of the point spread function (PSF).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…In [6] variable demodulation frequency was used to obtain shifted sampling in the image space for in-plane SR. In [7] the authors compared the combination of images acquired at the same sample points in k-space but shifted afterwards, and the combination of the same number of images acquired at shifted positions through changes in demodulation frequency. They found that the HR images obtained by the latter method contained additional details in the form of image features, suggesting that new information was added through a denser sampling of the point-spread function (PSF).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent article, Tieng et al studied a super-resolution MRI technique, which relies on the combination of several low-quality images (same field-of-view and resolution) that are shifted against each other by a fraction of a pixel (1). Because additional (new) information is required in these images to improve the in-plane resolution by super-resolution principles, the authors investigated whether small changes in the demodulation frequency of the MRI acquisition may lead to images with different information content.…”
mentioning
confidence: 99%